There’s More to Marriage Than Love: The Effect of Legal Status and Cultural Distance on Intermarriages and Separations - Adda, Jérôme; Pinotti, Paolo; Tura, Giulia (Journal of Political Economy, 2025)
We analyze the contribution of legal status incentives on the marriage choices of natives and migrants. Access to legal status reduces the probability of immigrants intermarrying with natives by 40% and increases the hazard rate of separation for intermarriages by 20%. We develop and estimate a multidimensional equilibrium model of marriage, fertility, and separation, where individuals match on observed and unobserved characteristics. Allowing for trade-offs between cultural distance, legal status, and other socioeconomic spousal characteristics, we quantify the role of legal status and the strength of cultural preferences and evaluate the welfare consequences of granting legal status to immigrants.